CULTURAL VALUES OF WOMEN AND MARRIAGE IN AL-‘ARABIYYAH BAYNA YADAIK AND AL-KITAB FI TA‘ALLUM AL-‘ARABIYYAH - Fatwa Arifah; Emzir Emzir; Sukron Kamil (Arabi : Journal of Arabic Studies, 2020)
The aim of this study is to find deep information about cultural values contained in al-Kitab fi Ta‘allum al-‘Arabiyyah and al-‘Arabiyyah bayna Yadaik  related to women and marriage. This study used a qualitative approach with the content analysis method by Norman Fairclough's Critical Discourse Analysis which is limited to the linguistic aspect. The text describes the problems faced by women regarding the culture of marriage and reveals cultural values related to the role of women in society and their position in marriage. The result of this study confirmed that al-Kitab fi Ta'allum al-'Arabiyyah and al-'Arabiyyah bayna Yadaik represent women and their position in marriage and society with a multi-perspective way.  This study is important to provide critical thinking about women's issues and marriage in Arabic language teaching. Furthermore, the student and teacher will have an awareness and understanding of cultural differences to increase their ability to communicate with Arab society.